PENDAMPINGAN BELAJAR BAHASA INGGRIS DI OEMAH NGAJI, DESA TURI, SLEMAN, YOGYAKARTA - Maryani Maryani; Risa Arroyyani (Bajang Institute, 2022)
The English learning assistance community service aims to give knowledge of the use of basic English and vocabulary mastery, word order, and sentence order correctly. This training activity involved the students. Mentors in this activity were English lecturers who have good English skills and mastery. The implementation of the mentoring activities took place at Oemah Ngaji Arjosari, Turi, Sleman, Yogyakarta. This training was held to improve students' English language skills. The results of the activity showed that the students were very enthusiastic to participate in the learning activity which could be seen from their activeness and presence during the mentoring. From this training activity, it is expected that the students' English skills will improve.